#TITLE_ALTERNATIVE# - ADRYANTA BANGUN (NIM 13202106), ARNE
Transient phenomenon such as lightning could be happened any time unpredictably. Because of this unpredictable phenomenon, spikes could arise by transfer energy as high current or voltage through conductor which connected to electronic instruments. If this transient enters some set of electronics, this transient will occur a very high current impulse which the one may cause damage to the electronic devices in it. The damage could be happened because the current which enters the instruments exceeds the limit of the electronic instrumentation's specification which has been specified before. Hence, surge protection at thousands of signal line interfaces provides reliable, continued performance from damaging voltage spikes using the silicon Transient Voltage Suppressor (TVS) devices. To avoid this damage, Device and IC processing Lab. MicroElectronic-ITB develops an avalanche diode device which its structure is called Guard Ring which will give protection to some set of electronics from the transient phenomenon. This device is made of p+ type, n-type and p type junctions. The special qualities of this guard ring avalanche diode compared with the common diodes are the suppressing of leakage current and avalanche noise. The characteristic of this device is the impact ionization breakdown. The device we developed can work on the 200 Volt + 20% which produces 10 Ampere current or able to be passed by a 2000 Watt power. To prove its ability in eliminating the transient phenomenon which enters a set of electronics, some tests are peformed by using the SPICE simulator. The avalanche diode will be modeled by a set of circuit, while the electronics instrument will be modeled by a resistor. The test results shown, that bility of this guard ring structured avalanche diode can suppress 97% of the transient phenomenon which may occur damage to the set of electronics.